Brazilian Protocol for Sexually Transmitted Infections 2020: viral hepatitis - Duarte,Geraldo (2021)
Abstract This article discusses viral hepatitis, a theme addressed by the Clinical Protocol and Therapeutic Guidelines to Comprehensive Care for People with Sexually Transmitted Infections and, more precisely, by the Clinical Protocols and Therapeutic Guidelines for Hepatitis B and Hepatitis C and Coinfections, published by the Brazilian Ministry of Health. Besides the broad spectrum of health impairment, hepatitis A, B, and C viruses also present different transmission forms, whether parenteral, sexual, vertical, or fecal-oral. Among the strategies suggested for the control of viral hepatitis, in addition to behavioral measures, are expanded diagnosis, early vaccination against hepatitis A and hepatitis B viruses, and access to available therapeutic resources. Considering vertical transmission of the hepatitis B and hepatitis C viruses, screening for pregnant women with chronic hepatitis B and C is an essential perinatal health strategy, indicating with precision those who can benefit from the prophylactic interventions.